Populism, familialism, and borders: the interplay of family and anti-Muslim immigration policies in Hungary - Linnamäki, Katinka (Frontiers in Political Science, 2024)
Immigration and the defense of national borders have played a vital role in European right-wing populist discourses since the European border crisis in 2015. Western European populist anti-immigration policies are often intertwined with gender politics (as in femonationalism and homonationalism). Research on Central and Eastern Europe offers the opportunity to examine the relationship between populist, “illiberal” family mainstreaming and anti-immigration policies. The aim of this article is to fill a gap in literature, addressing a direct connection between the Hungarian government’s family politics and anti-Muslim immigration policies. How has an ideological understanding of “family” legitimated the Hungarian government’s border politics since 2015? This question is addressed using qualitative content analysis and framing analysis to examine government material dated 2015–2023 (Modifications of the Fundamental Law, National Consultations, and material related to the Budapest Demographic Summit). The article demonstrates how border politics are informed and legitimated by discourses around Christian “families.” An antagonism between “illiberal” family policies and “liberal” immigration policies is forged around two discursive frames: economics and human rights. According to the government, pro-immigration border policies threaten the sustainability of its family policies—and indirectly the Hungarian “families” —as both are fighting for finite economic resources. Besides, it is argued that mass Muslim immigration threatens Hungary’s national self-identity, which is strongly rooted in Christianity and familialism. The results suggest that family politics, beyond serving as a biopolitical tool, provide an ideological platform on which nationalism, populism, and illiberalism are effectively merged as the foundation of the Hungarian government’s “illiberal” politics. In its ideological sense, “family” acts as a signifier for the “illiberal” political community. In this context, immigration is framed not solely as a biopolitical threat, but is used by the Hungarian government to discursively constitute a frontier of “us.” This frontier is primarily drawn between “us” and the European Union’s pro-immigration policies, and only indirectly between “us” and the immigrants themselves.